COVID-19 Calls for Mathematics, Part 2: Interleukin IL-6 and Myo-Inositol, Suicide-substrate Enzyme Inhibitors - Mascia, Corrado; Bernuzzi, Paolo; Esposito, Rachele; Massimi, Alessandra; Pallicca, Francesca; Sanna, Alessio; Simeoni, Chiara (Organisms. Journal of Biological Sciences, 2020)
Interleukin IL-6 is a cytokine produced in response to various types of damage (infections, tissue injuries, autoimmune diseases, etc.) whose action contributes to host defense through stimulation of acute phase responses and immune reactions. However, experimental data show that high concentration levels of interleukin IL-6, and the subsequent inflammatory cascade induced into the organisms, could lead to several complications, such as organs progressive deterioration. The abnormal release of interleukin IL-6 is also a consequence of SARS-CoV-2 virus contagion, usually causing interstitial pneumonia and respiratory failure, which appear to be the source of decease in most of patients. Tocilizumab and myo-Inositol are two possible remedies proposed in the clinical literature to contrast the uncontrolled synthesis of interleukin IL-6, although the former exhibits non negligible collateral effects, differently from the latter. For this reason, the mathematical investigation of myo-Inositol interaction with other relevant substances involved in the SARS-CoV-2 could support the bio-medical research in determining, the optimal doses and admin- istration timing necessary to minimize damages, in order to support the clinical results. The preliminaries of this approach are the subject of this article. Moreover, because a vaccine against the SARS-CoV-2 virus will not be available shortly, we con- sider another possible pharmacological strategy to contrast its activity. There exist several candidate medicines which may inhibit infec- tion and replication of SARS-CoV-2, and we focus our attention on the process of enzymatic inhibition through mechanism-based enzyme inactivators. The so-called suicide- substrate strategies constitute a fascinating area of interdisciplinary research. We explain the procedure to represent mathematically how a hypothetical drug would act to inhibit the essential enzymes used by the SARS-CoV-2 virus to replicate and spread. Considering the biological aspects and the mathematical applications presented in this article, the more relevant questions which arise are: 1) does the design of these drugs deserve a more detailed investigation? Could they be a viable alternative to the strategy of massive vaccine campaign against the SARS-CoV-2 virus? Citation: Bernuzzi, P, Esposito, R, Mascia, C, Massimi, A, Pallicca, F, Sanna, A, Simeoni, C, 2020, “COVID-19 calls for Mathematics, Part 2: Interleukin IL-6 and Myo-Inositol, Suicide-substrate Enzyme Inhibitors”, Organisms: Journal of Biological Sciences, vol. 4, no. 1, pp. 128-139. DOI: 10.13133/2532-5876/16969.